1997
DOI: 10.1007/s002469900126
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Analysis of Common Atrioventricular Valves in Patients with Right Atrial Isomerism

Abstract: The objective of the study was to examine the relation between the morphology of the common atrioventricular valve and regurgitation of the valve in patients with right atrial isomerism. We examined seven consecutive patients with documented right atrial isomerism who subsequently underwent postmortem examination during a 10-year period. The degree of regurgitation and the diameters of the common valve were evaluated via cineangiography, and the site of regurgitation was evaluated by echocardiography. The morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The choice of repair procedure for patients with FSV is an important issue. AVV morphology varies widely, especially with atrial isomerism, 12,13 and the decision regarding the repair procedure must be based on the preoperative and intraoperative morphologic findings. Therefore, it is most important to reproduce the preoperative echocardiographic findings of the AVV with a reasonable operative field; otherwise, the surgeon may repair an area that has no regurgitation preoperatively, and the AVV may be deformed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of repair procedure for patients with FSV is an important issue. AVV morphology varies widely, especially with atrial isomerism, 12,13 and the decision regarding the repair procedure must be based on the preoperative and intraoperative morphologic findings. Therefore, it is most important to reproduce the preoperative echocardiographic findings of the AVV with a reasonable operative field; otherwise, the surgeon may repair an area that has no regurgitation preoperatively, and the AVV may be deformed.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that regurgitant AVV in patients with FSV is mostly caused by structural abnormalities, including abnormal clefts and commissures, dysplastic leaflets, and elongated or shortened chordae, 1,2,10 especially in cases of atrial isomerism. 12,13 Therefore, in later cases, we favored commissural annuloplasty and closure of abnormal clefts or commissures (leaflet apposition), 6 attempting to preserve the normal or functional leaflets and commissures. 5.…”
Section: Operative Techniques and Managementmentioning
confidence: 99%
“…Furthermore, Inamura's case 4 and one of our cases had moderate regurgitation across the common atrioventricular valve. Dilation of the atrium, associated with regurgitation of the common atrioventricular valve, which is often encountered in patients with right isomerism and is known to carry a poor prognosis, 6 may also be a factor associated with the compression of the pulmonary vein connecting to the atrium with a morphologically right appendage.…”
Section: 'mentioning
confidence: 99%
“…Previous studies have shown an incidence of 5–12 % of systemic outflow stenosis in patients with RAI (Eronen et al 2013; Ota et al 2012; Kawahira et al 1997). Systemic outflow stenosis may increases the difficulty of the operation.…”
Section: Cardiac Lesionsmentioning
confidence: 96%
“…AVV regurgitation in RAI is primarily caused by structural abnormalities, including abnormal clefts and commissures, dysplastic leaflets, and elongated or shortened chordae (Uemura et al 1998; Kawahira et al 1997). Ota et al (2012) reported that 13 (21.7 %) patients with RAI had severe systemic AVV regurgitation on their first echocardiogram.…”
Section: Cardiac Lesionsmentioning
confidence: 99%